Spatial distributions of radionuclides deposited onto ground soil around the Fukushima Dai-ichi Nuclear Power Plant and their temporal change until December 2012. (January 2015) - Mikami, Satoshi; Maeyama, Takeshi; Hoshide, Yoshifumi; Sakamoto, Ryuichi; Sato, Shoji; Okuda, Naotoshi; Demongeot, Stéphanie; Gurriaran, Rodolfo; Uwamino, Yoshitomo; Kato, Hiroaki; Fujiwara, Mamoru; Sato, Tetsuro; et al.
Abstract: Spatial distributions and temporal changes of radioactive fallout released by the Fukushima Dai-ichi Nuclear Power Plant accident have been investigated by two campaigns with three measurement schedules. The inventories (activities per unit area) of the radionuclides deposited onto ground soil were measured using portable gamma-ray spectrometers at nearly 1000 locations (at most) per measurement campaign. Distribution maps of the inventories of 134 Cs, 137 Cs, and 110m Ag as of March, September, and December 2012 were constructed. No apparent temporal change of the radionuclide inventories was observed from March to December 2012. Weathering effects (e.g., horizontal mobility) were not noticeable during this period. Spatial dependence in the ratios of 134 Cs/ 137 Cs and 110m Ag/ 137 Cs were observed in the Tohoku and Kanto regions. The detailed maps of 134 Cs and 137 Cs as of September 2012 and December 2012 were constructed using the relationship between the air dose rate and the inventory. Graphical abstract: Highlights: Maps of 134 Cs, 137 Cs and 110m Ag on March, September and December 2012 were created. Deposited radionuclides inventories did not change from March to December 2012. Spatial variations in 134 Cs/ 137 Cs and 110m Ag/ 137 Cs ratio were observed. Detailed maps of 134 Cs and 137 Cs were created from the air dose rate measurements.